Análise espermática e histopatologia testicular de touros Nelore suplementados com caroço de algodão e glicerina - Tsuneda, Pedro Paulo (2015)
The agro-industrial byproducts, once considered a problem for nature, resurface demonstrating its potential, due to its power to replace traditional foods, reducing the cost of food. In the biodiesel production process also leads to glycerin, glycerol content which can vary from 80 to 90%, with a potential for use in ruminant diets, replacing energy grains such as corn. However, there are suspicions that the glycerol in the diet can interfere with sperm breeding parameters. Another byproduct agribusiness to be explored by cost advantages and functionality is the cotton seed, that it is not for human food and its composition is rich in energy and protein. But in all cotton plant structures there is a toxin called gossypol. Papers state that gossypol promotes reduction in the concentration, inhibition of motility and increased sperm mortality. The main objective was to assess whether the cottonseed and crude glycerin as ingredients in multiple supplements for Nellore finishing phase during the wet season interfered in semen parameters and testicular histopathology. We used 40 Nellore with initial weight of 472 ± 23.23 kg and mean age of 30 months. The animals were fed diets with two cottonseed levels (0 and 25%) and two crude glycerin levels (0 and 15%) in multiple supplements, with the treatments: SP (concentrate with no added co-products containing 0% 0g glycerol and gossypol), CA (concentrate 25% with the inclusion of seed cotton-containing 0% glycerol and Gossypol 50g / day), GLIC (Concentrate with inclusion of 15% glycerol containing 15% glycerol / MS and 0g Gossypol) and CAGLIC (concentrate 25% with the inclusion of cottonseed and 15% glycerol containing 15% glycerol / MS and Gossypol 50g / day), providing up 4 kg / animal / day supplements. The variables of seminal parameters analyzed were: volume, motility, vigor, concentration, plasma membrane integrity integrity of acrosome membrane, percentages of minors, major and total abnormalities. Together with evaluation of semen parameters were evaluated possible histological changes of testicular parenchyma. The plasma membrane integrity suffered negative interference (P <0.05) by treatment CAGLIC (23.062 ± 14.63) compared to the GLIC and AC group (49.784 ± 17.60) and (13.02 ± 48.039) respectively. In the variables: volume, motility, vigor, concentration, acrosome membrane integrity, percentages of total abnormalities, minor abnormalities and higher there was no influence of the treatments (P> 0.05). There was no difference between treatments on the testicular histology. Glycerin and the cotton seed in the levels used in the energy substitution of corn and protein soybean meal in diets bulls did not affect the sperm quality and testicular histology of players.